The effect of motivation and self-efficacy on academic performance with burnout as a mediation variable - Jannah, Wardatul; Rivai, Harif Amali; Syahrul, Laura (Jurnal Mantik, 2024)
The purpose of this research is to analyze the factors which cause students' academic performance in completing their education, including motivation and self-efficacy regarding academic performance with burnout that the students feel as a mediation variable. Academic performance is an important thing that must be considered by the management of an educational institution in achieving educational goals. The population in this study are active students of the Sapta Samudra Padang Maritime Academy with a sample of 96 active students of the class of 2019-2022. The analysis method used descriptive statistical analysis and factor description analysis using SmartPLS 4.0. The results of this study shows that motivation and self-efficacy have a positive and significant effect on burnout; motivation and self-efficacy have a positive and significant effect on academic performance; burnout has a negative and significant effect on academic performance; burnout as a mediating variable has a partial mediation effect in mediating motivation on academic performance and burnout as a mediating variable also has a partial mediation effect in mediating the relationship between self-efficacy and academic performance